Lālana Phakirera samāja cetanā - Biśvāsa, Kuñjabana (Akṣara Prakāśanī, 2023)
Study on social consciousness in the works of Lālana Śāha, 1774-1890, Bengali nomadic folk poet from Kushtia in undivided Bengal, India, now part of Bangladesh.
Literaturverzeichnis: Seite 111-112
Keywords: Lālana Śāha; 1774-1890; Criticism and interpretation.; Social problems in literature.